Cerebral involvement with disseminated intravascular coagulation in intestinal disease. Issue 6 (June 1977) - Ryan, F P; Timperley, W R; Preston, F E; Holdsworth, C D
Abstract : Over a two-and-a-half-year period at the Sheffield Royal Infirmary, six patients developed disseminated intravascular coagulation as a serious complication of intestinal disease. There was clinical evidence of cerebral involvement in all six patients, and small vessel thrombi were demonstrated in the brains of all three cases examined post mortem. Where the true significance of the cerebral disorder was not recognised, this led to delay in the diagnosis with serious risk to the patient. In the single case in which the diagnosis was made early, the intravascular coagulation was completely reversed with heparin therapy.